Cordas cósmicas e gravitação planar de ordem superior - Lobo, M. P [UNESP] (2008)
The possibility of generalizing gravity in 2+1 dimensions to include higher-derivative terms, thereby allowing for a dynamical theory, opens up a variety of new interesting questions. This is in great contrast with pure Einstein gravity which is a generally covariant theory that has no degrees of freedom - a peculiarity that, in a sense, renders it a little insipid and odorless. The research on gravity of particles moving in a plane, that is, living in flatland, within the context of higher-derivative gravity, leads to novel and interesting effects. For instance, the generation of gravity, antigravity, and gravitational shielding by the interaction of massive scalar bosons via a graviton exchange. In addition, the gravitational deffection angle of a photon, unlike that of Einstein gravity, is dependent of the impact parameter. On the other hand, the great drawback to using linearized general relativity for describing a gravitating string is that this description leads to some unphysical results such as: (i) lack of a gravity force in the nonrelativistic limit; (ii) gravitational deffection independent of the impact parameter. Interesting enough, the effective cure for these pathologies is the replacement of linearized gravity by linearized higher-derivative gravity. We address these issues here